Virtual Reality as a New Approach for Risk Taking Assessment - de-Juan-Ripoll, Carla; Soler-Domínguez, José L.; Guixeres, Jaime; Contero, Manuel; Álvarez Gutiérrez, Noemi; Alcañiz, Mariano (Frontiers in Psychology, 2018)
Understanding how people behave when facing hazardous situations, how intrinsic and extrinsic factors influence the risk taking (RT) decision making process and to what extent it is possible to modify their reactions externally, are questions that have long interested academics and society in general. In the spheres of Occupational Safety and Health (OSH), the military, finance and sociology, this topic has multidisciplinary implications because we all constantly face risk taking situations. Researchers have hitherto assessed risk taking profiles by conducting questionnaires prior to and after the presentation of stimuli; however, this can lead to the production of biased, non-realistic, risk taking profiles. This is due to the reflexive nature of choosing an answer in a questionnaire, which is remote from the reactive, emotional and impulsive decision making processes inherent to real, risky situations. One way to address this question is to exploit VR capabilities to generate immersive environments that recreate realistic seeming but simulated hazardous situations. We propose VR as the next-generation tool to study risk taking processes, taking advantage of the big four families of metrics which can provide objective assessment methods with high ecological validity: the real-world risks approach (high presence VR environments triggering real-world reactions), embodied interactions (more natural interactions eliciting natural behaviours), stealth assessment (unnoticed real-time assessments offering efficient behavioural metrics) and physiological real-time measurement (physiological signals avoiding subjective bias). Additionally, VR can provide an invaluable tool, after the assessment phase, to train in skills related to risk taking due to its transferability to real-world situations.